2012
DOI: 10.1182/blood-2011-07-370841
|View full text |Cite
|
Sign up to set email alerts
|

High ERp5/ADAM10 expression in lymph node microenvironment and impaired NKG2D ligands recognition in Hodgkin lymphomas

Abstract: Herein we describe that in classic Hodgkin lymphomas (cHL, n ‫؍‬ 25) the lymph node (LN) stroma displayed in situ high levels of transcription and expression of the disulfide-isomerase ERp5 and of the disintegrin-metalloproteinase ADAM10, able to shed the ligands for NKG2D (NKG2D-L) from the cell membrane. These enzymes were detected both in LN mesenchymal stromal cells ( IntroductionIt is now accepted that the so-called stress surveillance contributes to the anti-neoplastic immunity, both in solid tumors and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 49 publications
2
93
0
Order By: Relevance
“…Previous studies showed that ADAM10 is required for normal PC function (43), and its expression increases during B cell differentiation, reaching higher levels at the PC stage (44). However, no evidence is available for the malignant cell counterpart, although a role for ADAM10 in hematologic malignancies was recently reported (45,46). Importantly, we provide evidence that ADAM10 expression is enhanced in MM cell lines and in primary PCs in response to genotoxic agents, and its upregulation requires ROS generation and is associated with the acquisition of a senescent phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that ADAM10 is required for normal PC function (43), and its expression increases during B cell differentiation, reaching higher levels at the PC stage (44). However, no evidence is available for the malignant cell counterpart, although a role for ADAM10 in hematologic malignancies was recently reported (45,46). Importantly, we provide evidence that ADAM10 expression is enhanced in MM cell lines and in primary PCs in response to genotoxic agents, and its upregulation requires ROS generation and is associated with the acquisition of a senescent phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…LNMSC were isolated and cultured as described (Online Supplementary Appendix). 30,31 Co-cultures of LNMSC and Vd2T lymphocytes, or LNMSC and autologous LN cell suspensions were perfomed at the ratio of 1:10.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence was performed as described. 31 Samples were run on CyAnADP flowcytometer (Beckman Coulter). Results are expressed as log mean fluorescence intensity (MFI) or percentage of positive cells.…”
Section: +Lnmsc +Lnmscmentioning
confidence: 99%
See 2 more Smart Citations